Regenerable Sorbents for High‐Temperature Desulfurization of Syngas from Biomass Gasification. Issue 6 (6th April 2021) - Ma, Jianyu; Mahmoodinia, Mehdi; Rout, Kumar R.; Blekkan, Edd A.
Abstract: Single‐metal high‐temperature solid sorbents for syngas cleaning using Mn, Ca, Fe, Cu, or Mo supported on γ ‐Al2 O3 were synthesized, characterized, and tested in a fixed‐bed reactor. H2 S and SO2 concentrations in the gas after treatment at T = 400 to 700 °C were compared with thermodynamic calculations. The Mn‐based sorbent showed the best ability to achieve a low sulfur residual in the gas, especially at temperatures above 600 °C. Sorbents with Fe, Cu, and Mo gave SO2 formation in the initial phase, but this could be avoided by a pre‐reduction treatment of the sorbent material. Abstract : High‐temperature sulfur sorption can reduce the investments and operating costs linked with gas cooling for the cleaning step and reheating before further processing and fuel synthesis. In this paper, the capacity and lowest attainable sulfur level of supported metal sorbents are investigated.